(untitled) (Academic journal Industrial Machine Building Civil Engineering, 2017)
Design features of uncapital ungirder frame structure of building are presented: the component elements, the advantages and disadvantages, usage experience. Problem of affordable housing in Ukraine, which is relevant now successfully solved by the implementation into construction uncapital ungirder frame structure of building. The frame consists of the smallest number of precast concrete structures sizes, which are manufactured at plants. The component elements of the system that have been tested in the laboratory of the department of reinforced concrete and masonry structures and strength of materials Poltava National Technical Yuri Kondratyuk University are presented. The examples of buildings, which constructed on this constructive system in Poltava are provided. Keywords: Uncapital Ungirder Frame Structure, constructive system, affordable housing.